2016
DOI: 10.1007/s40808-016-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of land use/land cover pattern changes in Arasbaran Biosphere Reserve: Iran

Abstract: Main global environment and ecological functions and structure affected by land use/cover changes (LUCC). Analysis of the dynamic LUCC can be very useful in biosphere reserves (BRs) management. The Land use and cover (LULC) spatio-temporal changes in the Arasbaran BR were classified (as Agricultural, Forest and Barren/Range lands), and compared with future spatial pattern (simulated using the CA-Markov model) to evaluate qualitative and quantitative changes of this BR LULC over time (1989, 2000 and 2013 with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Numerous previous studies have examined the simulation of land use changes pattern by using a CA-Markov model. Parsa et al [24] successfully used the CA-Markov model in Arasbaran biosphere reserve-Iran to predict the future LULC, which serves land use planners and policy makers in order to make appropriate decisions for future land use challenges. They indicated that using a CA-Markov model can be useful in land use policy design and it may also be used as an early warning system.…”
Section: Background and Analysis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have examined the simulation of land use changes pattern by using a CA-Markov model. Parsa et al [24] successfully used the CA-Markov model in Arasbaran biosphere reserve-Iran to predict the future LULC, which serves land use planners and policy makers in order to make appropriate decisions for future land use challenges. They indicated that using a CA-Markov model can be useful in land use policy design and it may also be used as an early warning system.…”
Section: Background and Analysis Of The Literaturementioning
confidence: 99%
“…This model is often used in monitoring, ecological modelling, simulation changes, trends of the LULC and to predict the amount of the land use change and the stability of future land development in the area of interest [24,31,36]. Burnham [37] first used this model for land use modelling.…”
Section: The Markov Modelmentioning
confidence: 99%
“…The application of a CA-Markov model in predicting the growth of most buildings considers the following points. The integration of the CA-Markov model is considered to be valuable for modelling land-use changes and is able to simulate and predict changes [42,43]. The CA-Markov model is the combination of Cellular Automata and transition probability matrix generated by the cross tabulation of two different images [42].…”
Section: Optimal Iterations Of Ca-markov Model For Built-up Growth Prmentioning
confidence: 99%
“…Furthermore, the land-use changes for any location (cells) can be clarified by the existing state and changes in neighbouring cells and can simulate the growth of things in two directions. This model is broadly used in spatial model for predicting future land-use [43,46].…”
Section: Optimal Iterations Of Ca-markov Model For Built-up Growth Prmentioning
confidence: 99%
See 1 more Smart Citation